2008
DOI: 10.1051/0004-6361:20078666
|View full text |Cite
|
Sign up to set email alerts
|

Outburst activity in comets

Abstract: Aims. We carried out a continuous monitoring of comet 29P/Schwassmann-Wachmann 1 by using medium aperture telescopes with the aim of studying the activity and outburst mechanisms of this comet on the basis of photometric variations. Methods. We used a standardized method to obtain the coma photometry in the R filter of the Johnson-Kron-Cousins system. Some abrupt changes observed in the brightness of SW1 suggest important variations in surface activity with time.Results. During our 2002−2007 observational camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 22 publications
5
40
0
1
Order By: Relevance
“…2(b). We posted an alert to the astronomical community about this unusually bright outburst (Trigo‐Rodríguez et al 2010). On February 3.18 the first multiband photometry was obtained from the Gualba Observatory (MPC442), which shows the comet exhibiting a bright core characteristic of a massive outburst (Fig.…”
Section: Observational Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2(b). We posted an alert to the astronomical community about this unusually bright outburst (Trigo‐Rodríguez et al 2010). On February 3.18 the first multiband photometry was obtained from the Gualba Observatory (MPC442), which shows the comet exhibiting a bright core characteristic of a massive outburst (Fig.…”
Section: Observational Resultsmentioning
confidence: 99%
“…These ideal values are typically affected by seeing, so the effective resolution is between 1 and 2 arcsec, or roughly about 6300 km pixel −1 . Our experience says that such a resolution is good to follow the overall nuclear activity of this centaur using the above‐mentioned standard aperture (Trigo‐Rodríguez et al 2008).…”
Section: Observational Data and Reduction Proceduresmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the first two known Centaurs, 29P and 39P, are comets, discovered thanks to the extra brightness from the coma. In fact, 29P has probably never been seen inactive (Jewitt 1990; Meech et al 1993), but frequently observed to burst out at irregular time intervals and with a range of amplitudes (Trigo-Rodríguez et al 2008. The third known Centaur, Chiron, was discovered with 'stellar appearance' (Kowal & Gehrels 1977) and classified as asteroid (2060), but later developed weak activity, which earned it the additional comet number 95P.…”
Section: Introductionmentioning
confidence: 99%
“…The different outbursts of different comets are recorded to be phenomenologically distinct, from the large-scale dust jets (e.g. Comets Wild 2; Sekanina et al 2004 and 9P/Tempel 1; Farnham et al 2007), the periodic outburst events of P/Schwasmannn-Wachmann 1 (Hughes 1990;Trigo-Rodríguez et al 2008), to the massive outburst of 17P/Holmes (Montalto et al 2008). Similarly, explaining the outbursts in general terms proves to be difficult; however, the immediate cause(s) may be roughly separated into external sources (impacts), physicochemical exothermic processes inside the nucleus (phase changes, etc.…”
Section: Introductionmentioning
confidence: 99%